Credibility of Digital Comic Media in Audio Visual Form on Style Topic for Elementary School Students - I Putu Oka Sastrawan; I Gede Margunayasa; Gede Wira Bayu (Universitas Pendidikan Ganesha, 2021)
Lack of teacher creativity in learning to develop instructional media makes learning less effective. Therefore, it is necessary to develop media that can make students enthusiastic about learning, such as digital comics. This research produces a product in the form of Digital Comic media on elementary school student style whose validity has been tested. The model used is the ADDIE model with the stages of Analyze, Design, Development, Implementation, Evaluation. In this study, digital comic media used as research subjects were 2 media expert lecturers, 2 material experts, 2 teachers. The method and instrument of data collection in this study is to use the rating scale method. To measure the validity of digital comic media using an instrument to assess the validity of digital comic media. The results of the data that have been obtained will be analyzed using the Aiken validity index formula for expert data and the mean formula for respondents' data in order to determine the validity of digital comic media. The results of the media validity on the Aiken validity index analysis, the assessment of the experts, got a score of 0.95 from the material experts with the criteria of